Parascapular sub-iliocostalis plane block for postoperative analgesia in patients with multiple rib fractures: a randomized controlled trial - Qiji Ju; Ping Li; Long Zhang; Liangguang Zhang; Guanyi Liu; Liyong Yuan; Miao Zhu (BMC Anesthesiology)
Abstract Background Patients with multiple rib fractures (MRFs) often experience severe postoperative pain. The parascapular sub-iliocostalis plane (PSIP) block holds promise as an effective method for analgesia, warranting further investigation and validation. Methods In this double-masked randomized trial, eligible MRF patients underwent surgery and were allocated to receive either preoperative PSIP block (intervention) or standard care (control). Postoperative outcomes including pain trajectories (serial VAS assessments), analgesic consumption, hemodynamic stability, recovery metrics (QoR-15), and adverse events were systematically evaluated. Statistical analyses adhered to intention-to-treat principles. Results The AUC0.5−24 of VASpain curves of Group PSIP was lower (P = 0.016). The VASpain of Group PSIP were lower at 0.5 h, 2 h, 6 h, 12 h, and 24 h after the extubation (P < 0.001, 0.005, < 0.001, 0.020, 0.029). There was a decrease in VASpain in Group PSIP after blocking (P < 0.001). Patients in Group PSIP required a lesser amount of analgesics within the initial twenty-four hours following surgery (P = 0.026). Group C had a significantly earlier use of analgesics (P < 0.001). At the time of skin incision, fracture reduction, suture and after extubation, Group PSIP had a lower MAP (P = 0.002, < 0.001, 0.003, 0.001) and AUC of MAP curves (P = 0.039). The Group PSIP exhibited lower Ricker scores in PACU, along with shorter observation times as well (P = 0.005, 0.046). The severity of PONV within 24 h post-surgery in the Group PSIP was also lower (P = 0.013). Moreover, at the 24 h post-surgery, the QoR-15 score was higher in Group PSIP (P = 0.025). Conclusions The PSIP block demonstrated efficacy in managing postoperative pain in patients with MRFs, mitigating intraoperative hemodynamic fluctuations and agitation during resuscitation, and enhancing short-term recovery outcomes following surgery.